The Degree of Islamic Education Teachers’ Commitment for the Teaching Career Ethics from the School Principals’ Viewpoint in Jerash Governorate - Al-Harahsheh, Ahmad Ahmoud (Journal of Educational and Psychological Sciences, 2021)
The study aims to recognise "The Degree of Islamic Education Teachers’ Commitment for the Teaching Career ethics from the School Principals’ Viewpoint in Jerash Governorate. The researcher uses the analytical method. The sample is 80 male and female school principals who are chosen randomly. The questionnaire consists of 54 paragraphs divided into four fields. These fields are the relationship between Islamic Education Teachers and their career (paragraphs 1_14), their relationship with their students (paragraphs 15_30), their relationship with their colleagues (paragraphs 31_44), and the fourth field is the relationship between Islamic Education Teachers and the local society (paragraphs 45_54), The study finds that "The Degree of Islamic Education Teachers’ Commitment for the Teaching Career Ethics from the School Principals’ Viewpoint in Jerash Governorate" comes generally with high degree. The average of the fields come in the following ascending order: the relationship between Islamic Education Teachers and local society, their career, their students, their colleagues. Also, the results show there are no differences with statistical evidence in their degree of commitment for teaching career ethics according to gender, level of education, experience or the type of university. The study recommends to hold courses and workshops for teachers, school principals and supervisors to enlighten them with the importance of the commitment of teaching career ethics. In addition, it recommends to prepare an ethical charter for new teachers to follow it from the beginning of their work.